Using the electronic medical record to increase testing for HIV and hepatitis C virus in an Appalachian emergency department - Carmen N. Burrell; Melinda J. Sharon; Stephen Davis; Judith Feinberg; Elena M. Wojcik; Julia Nist; Owen Lander; Valerie Boley; Justin Burns; Ian B. K. Martin (BMC, 2021)
Abstract Background The ongoing Appalachian opioid epidemic has led to increasing hepatitis C virus (HCV) infections among people who inject drugs (PWID), and Human Immunodeficiency Virus (HIV) outbreaks have been observed. The primary aim of this study was to assess the potential increase in screening for HIV and HCV in an academic central Appalachian emergency department (ED) through the use of Best Practice Alerts (BPAs) in the electronic medical record (EMR). A secondary aim was to assess for an increase in linkage to care using patient navigators. Methods EMR algorithms based on current Centers for Disease Control and Prevention HIV and HCV testing recommendations were created that triggered Best Practice Alerts (BPAs), giving providers a one-click acceptance option to order HIV and/or HCV testing. Placards were placed in care areas, informing patients of the availability of routine screening. Patient navigators facilitated linkage to care for seropositive patients. Results The BPA appeared 58,936 times on 21,098 patients eligible for HIV screening and 24,319 times on 11,989 patients eligible for HCV screening over a one-year period. Of those, 7106 (33.7%) patients were screened for HIV and 3496 (29.2%) patients were screened for HCV, for an overall testing increase of 2269% and 1065% for HIV and HCV, respectively. Linkage to care increased by 15% for HIV to 100, and 14% for HCV to 64%. Conclusion HIV and HCV screening and linkage to care were increased in an academic ED setting in central Appalachia using EMR alerts. This approach could be utilized in multiple ambulatory settings. Increased testing and earlier linkage to care may help combat the current injection drug use-related HCV epidemic and avoid additional HIV outbreaks.